(untitled) (Bangladesh Journal of Agricultural Research, 2023)
Justifiable, nutritious and safe food productions are main challenges for food safety which reduce starvation, meets dietary needs and food preferences for a healthy life. Home gardens can play a significant role in providing better food supply and diversity of food. Studies on niche-based homestead gardening were carried out at FSRD site Atia, Tangail under On-Farm Research Division of Bangladesh Agricultural Research Institute during 2018-19 and 2019-20 to utilize the homestead resources for producing vegetables and fruits and to enhance nutritional security for the farm families. A total of 12 households were selected from marginal (0.021–0.20 ha), small (0.21–1.0 ha) and medium (1.0- 3.0) farmer groups and seven production niches were intervened for year-round production following the Palima model. Results revealed that homestead area could be capable of harvesting sufficient and diversified vegetables round the year by utilizing all possible homestead nieches. After intervention, the number of vegetables was produced by medium farmers (630 kg/year) followed by small (510 kg/year) and marginal (408 kg/year) farmers. Yearly vegetable requirements of farmers were largely met by homestead garden with a supply between 30-58 kg/head/year compared with bench mark level of 5-12 kg/head/year. Results suggested that farmers consumed lion share of their products that could meet up nutrition. Utilization of farm resources available in the farm that increased nutritional security, income and improved livelihoods as well. The up scaling of the production model based on ecosystem in different poverty-stricken regions of Bangladesh is recommended to attain food security and lessening malnutrition. Bangladesh J. Agril. Res. 47(1): 51-68, March 2022